Pentingnya Laporan Keuangan untuk Menilai Kinerja Suatu Perusahaan - Dharma, Budi; Ramadhani, Yus; Reitandi, Reitandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Performance is measured by the capital adequacy, liquidity and profitability indices, which together paint a picture of the state of a financial organization over a certain period of time both from the aspect of raising funds which can be seen from the indicators of capital held. Managing organizational operations, assisting in decision making, identifying employee training and development needs, providing feedback to employees on how their superiors perceive their performance, and providing a basis for award distribution are all advantages of performance appraisal for management. The purpose of this study is to determine the value of financial reporting in evaluating business performance. Research is useful for businesses because it provides information about the importance of financial statements in evaluating company performance and making decisions in the future. Researchers can learn how important financial reports are to assess the success of this research. This study uses a naturalistic approach, sometimes known as a qualitative approach. This study uses qualitative data, or information that is composed of words, sentences, or diagrams and pictures. The research data comes from secondary sources, or information obtained through documents, existing books, and literature studies. Keywords: Financial Statements, Financial Ratios, Financial Performance